Interpretation of orthotopic liver transplantation biopsy - Aryal, Gopi; Chhetri Aryal, Sameer (Journal of Pathology of Nepal, 2025)
Liver transplantation is an established treatment for various forms of severe liver disease due to any etiology, as well as selected metabolic and neoplastic conditions. Exposure to liver allograft biopsies among pathology residents is rare, particularly in a hospital where there is no liver transplantation program. Frozen-section evaluation of the liver of extended donor criteria confirms the quality /viability of the donor organ. It excludes features that would either contraindicate transplantation or increase the likelihood of various adverse short and long-term outcomes. Some liver transplant centers perform protocol liver biopsy after transplantation, even in those patients with normal liver function tests. Protocol biopsies are usually ordered at 1-, 3-, and 5-year post-transplantation.The Banff Working Group on Liver Allograft Pathology periodically updates its guidelines for studying liver allograft biopsies. In this review, we aim to provide a basic approach to interpret orthotopic liver transplant biopsies. This article may be beneficial for surgical pathologists, pathology residents interested in liver pathology, or gastrointestinal and liver pathology fellows in the early stages of their training.